Communication Patterns of The Persis Solo Boys 1923 Group Supporter Community (Qualitative Descriptive Study) - Hasyin, Fadhli; Sanjaya, Andika (Jogjakarta Communication Conference (JCC), 2025)
Persis Solo is an Indonesian Liga 1 football club owned by Kaesang Pangarep, the son of Indonesia’s seventh former president, Joko Widodo. Persis Solo has various supporter groups, one of which is Boys 1923. Boys 1923 is a supporter community that occupies the east stand, gate 8, of Manahan Stadium in Solo. This group embraces a casual ideology and holds the vision and mission of "no leader, just together." This study raises the question: what communication pattern is used by the Boys 1923 supporter community and how is this communication pattern implemented within the community. The purpose of this research is to identify the communication pattern used by the Boys 1923 community and understand how it is implemented. The method used in this research is descriptive qualitative, with data collected through in-depth interviews, observation, and documentation. Boys 1923 adopts a star communication pattern, where all members have equal standing and can influence one another, enabling optimal participation from every member. Strong interpersonal communication also plays a vital role in maintaining member relationships and building mutual trust. The principle of "from members, for members" forms the foundation of solidarity within the group. The applied communication pattern successfully enhances cohesion and cooperation among Boys 1923 members. This is reflected in their commitment to fully support Persis Solo, both at home and away matches, as well as their active participation in social activities. This study shows that an effective communication pattern is a key factor in fostering solidarity, loyalty, and cohesion within the Boys 1923 Persis Solo supporter community.